2006
DOI: 10.1002/cncr.21898
|View full text |Cite
|
Sign up to set email alerts
|

High‐risk cutaneous squamous cell carcinoma of the head and neck

Abstract: BACKGROUNDMost patients with cutaneous squamous cell carcinoma (cSCC) of the head and neck (HN) are at low‐risk (< 5%) of developing metastatic SCC to regional lymph nodes. However, patients with unfavorable clinicopathologic factors often are under appreciated by clinicians but remain at higher risk for developing metastatic lymph node disease and dying.METHODSPatients were identified who had metastatic cSCC to lymph nodes (parotid and cervical) of the HN and who were treated within the context of a multid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(82 citation statements)
references
References 38 publications
6
71
0
1
Order By: Relevance
“…In our univariate analysis, we found an association between local recurrence and the presence of perineural invasion, which is consistent with other studies. 673,698 Local recurrence was also associated with the presence of vascular invasion in our study. Poorly differentiated and undifferentiated tumours were significantly associated with increased mortality at 5 years from any cause and patients with such tumours were less likely to be alive with no history of recurrence at 5 years.…”
Section: Summary Of Number Of Patients Potentially Eligible For the Psupporting
confidence: 66%
“…In our univariate analysis, we found an association between local recurrence and the presence of perineural invasion, which is consistent with other studies. 673,698 Local recurrence was also associated with the presence of vascular invasion in our study. Poorly differentiated and undifferentiated tumours were significantly associated with increased mortality at 5 years from any cause and patients with such tumours were less likely to be alive with no history of recurrence at 5 years.…”
Section: Summary Of Number Of Patients Potentially Eligible For the Psupporting
confidence: 66%
“…Other anatomic pathologic criteria of the tumor should be considered, such as depth of invasion, histological differentiation grade, presence of perineural and lymphovascular invasion, because many patients in stages T1 and T2 may develop regional and distal metastases. 3,17 …”
Section: Discussionmentioning
confidence: 99%
“…16,21 Veness et al found 15% of recurrence in patients who had metastatic disease. 3 Another study found that 50% of SCC lesions with positive margins recurred with consequent increased risk of developing metastases. 22 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations